The Effect Of Natural Disasters On Idjâra (Rental) Contract In Islamıc Law - Mustafa Harun Kıylık (Van İlahiyat Dergisi, 2023)
In society, people need some properties themselves (the same) or for their own benefits. According to Islamic law, while people acquire the same properties they need through a bay' (sale) contract, they gain access to the benefits of the properties as a means of contracts such as idjāra (rent) or âriyya (lending). Muslims must conclude all kinds of contracts in accordance with the principles and conditions determined within the framework of the Quran and Sunnah. Otherwise, the contracts will be invalid or void. In terms of Islamic law, in a sales contract, the location which subjects to the contract must be existing, and possible to deliver. Since the sale of something that does not exist is prohibited, such a sales contract is void. However, some types of contracts, including the idjâra contract, are exempt from this rule based on some special evidence. Because the idjâra contract, which has been implemented since the time of legislation, is a mandatory need in human life, and also occupies an important place. For this reason, according to some jurists, the idjâra contract was not considered within the scope of the sale of the non-existent through istihsân, contrary to the general rule, and was accepted as legitimate on the grounds of istihsân. The fact that the İdjâra contract is established in a way that is contrary to analogy does not make it possible to compare other contracts with this contract. Since the contract of idjâra is one of the most frequently referred contracts after the contract of sale, it has been discussed in all its aspects by Islamic jurists and examined under separate headings. In this context, the impact of natural disasters on the idjāra contract has not been disregarded. In principle, a rent contract duly established with its provisions and conditions, as well as a sales contract, is binding on both parties. However, in unforeseen circumstances, especially during unexpected disasters, legal problems such as continuation of the rent contract, benefiting from the benefit of the rented property and refund of the paid fee arise. In our study, first of all, after briefly presenting what natural disasters mean in Islamic law literature, the nature of the idjā ra contract will be focused on, and then only the consequences of natural disasters on the rent contract will be detailed. As a result, in such disasters cause partial or total loss to the rented property, the possibility of continuation of the contract and the responsibilities of the parties will be revealed.